Genetic counseling program for patient with hyperglycemic syndrome - Ariyanto, Heri; Nurapandi, Adi; Purwati, Ayu Endang; Kusumawaty, Jajuk; Setiawan, Henri (Journal of Holistic Nursing Science, 2021)
Diabetes mellitus is a heterogeneous group of disorders characterized by hyperglycemia. In fact, diabetes is a disease that can occur due to genetic factors. The longer you have diabetes, the worse your quality of life will be. Interventions that can be used to improve the quality of life of patients by conducting genetic counseling. However, this intervention is still rarely implemented. Therefore, this study aims to assess the effect of genetic counseling on the quality of life in people with diabetes mellitus. This study used a Quasi-Experimental Without Control Group design with a pretest and posttest design. The sample used was 38 people, data collection was done by filling out a quality of life questionnaire (SF-36). A paired-Sample T-Test was used to test the hypothesis. Genetic counseling has an influence on the participants' quality of life (p < 0.05). This treatment needs to be carried out in daily nursing practice because there are benefits to the quality of life of diabetic patients.